Pusat Wisata Kuliner Khas Jawa Timur Dengan Konsep Arsitektur Tradisional Jawa Di Kota Malang - Aprilia Wulan Lestari; Tri Endangsih; Harfa Iskandaria (MAESTRO, 2023)
East Java is one of the provinces in Indonesia that offers various types of tourist attractions. Typical East Javanese cuisine has an appeal with a taste that uses a lot of shrimp paste and petis as a flavoring agent for food. The spicy and savory taste also attracts people to taste East Javanese culinary specialties. Many typical East Javanese dishes are cooked by boiling, frying, steaming and baking. In the city of Malang there are quite a lot of tourist objects that are visited by local and foreign tourists. With the number of visitors in 2018 there were 4 million visitors while in 2019 it jumped to 5 million in 2020 only 600 thousand due to the corona virus which caused a small number of tourists visiting. And in 2022 tourists visiting the city of Malang will also increase 3 times from January to June 2022, there will be 5.9 million. A culinary tourism center is a culinary tourism area that can meet the culinary needs of visitors and tourists as well as a place of recreation and refreshment where visitors can enjoy various culinary tours that reflect culture and characteristics. Based on the results of the analysis and conclusions in the discussion chapter, the authors propose the following goals and objectives: To design a culinary tourism center that can provide facilities and recreation that can be enjoyed by visitors and create a comfortable culinary and souvenir area typical of East Java. The problem with the architecture is how to design a culinary tourism center typical of East Java in the city of Malang with facilities that can meet all the needs and activities of the parties involved and what is the strategy to accommodate all activities at the center of culinary tourism typical of East Java. The research method used is a method with primary data collection techniques, direct surveys, and observation of secondary data case studies and literature surveys.